Edukasi Pencegahan Kekerasan Seksual pada Remaja di Sekolah Menengah Pertama Negeri 7 Muncang Desa Sindangwangi Kecamatan Muncang Kabupaten Lebak - Sierfi Rahayu; Tiwi Rizkiyani; Nikki Prafitri (P3M FIA UNKRIS, 2025)
The dominance of child abuse cases among adolescents at the junior high school level is a crucial problem. The community service activity carried out at SMPN 7 Muncang aims to provide understanding in the form of education about the importance of preventing sexual violence against adolescents. The method used is through community service with the stages of material delivery, question and answer discussions, and evaluation in the form of quizzes. This community service activity is one of the Student Work Lecture (KKM) programs of group 51 of Universitas Sultan Ageng Tirtayasa. Initial discussion by providing material on the types of violence and how to prevent and avoid sexual violence, then providing educational songs about preventing sexual violence. Seeing from the enthusiastic response of the students in this activity, the objectives expected in this service can be said to be achieved. well. The results of the activity showed that the students had a good understanding of the content and meaning of the material that had been delivered. The students were able to answer questions correctly and correctly, and were able to review very well the content of the material that had been delivered.